Entanglement : an investigation into the effective union of contemporary art and science communication : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Fine Arts at Massey University, Wellington, New Zealand - Hughes, Claire I. (Massey University, 2019)
Virtual reality (VR) technology is increasingly providing opportunities for new contemporary art experiences. This creative practice research has been developed to provide one such contribution. It offers innovative employment of the immersive capabilities of VR to engage with and convey complex scientific theories, and to stimulate changes in mental processes to unlock these concepts. The research highlights empirical similarities between art and science to propose that creative aspects of art can be considered proximate to the creative qualities required to understand quantum theories. In order to reveal this, the body of research engaged specifically with quantum entanglement, because of its well documented existence¹ combined with the more challenging considerations of how ‘communication’ can occur at a quantum level. By providing metaphoric immersive experiences of quantum entanglement, a contribution of ‘scientific communication’ is made as defined by the evocation of awareness, enjoyment, and interest, questioning of opinions and providing new perspectives of understanding.² This research posits that there is a fertile, effective terrain to explore in the union of the fields of contemporary art and science communication. Considerations of constructivist theories of knowledge and the concept of paradigm shifts³ are used whereby new insights into knowledge processes can be experienced through VR art. Here, simulacra, cognitive dissonance and the technological sublime afford a framework to create experiences of conflicting realities. It is due to the immersive strengths of VR which are exploited and subverted through my designs that these experiences can be facilitated for the viewer. The culmination of this research is Entangled, a VR art installation which provides interplays between virtual and physical spaces while also offering entry-points to contemplate and understand quantum theories. Critical analysis of this project is supported by focus group and questionnaire responses. These findings prove how viewers perceived the project as an aesthetic art work and that by recognising scientific underpinnings, an effective engagement and participation in elements of scientific communication occurred at varying levels. The work provided new perspectives on the properties of quantum entanglement. This facilitated cognitive and experiential awareness providing opportunities for viewers to encounter conflicting knowledge systems. The challenge in this creative practice research was to create aesthetic experiences that contravene common sense reasoning and provide insights into the type of thought processes and experiential perception that is required to deepen and expand our understanding of our physical reality. In the present era of an evolution of super-technologies, now past its nascent stage, Entangled offers exposure to the types of interfaces that this thesis asserts will increasingly be encountered when comprehending our reality in the 21st century and beyond.⁴ ¹ References to the proven existence of quantum entanglement are provided in section 1.6. ² This definition of scientific communication is expanded in section 1.1. ³ Paradigm shifts are times when the familiar framework has to be profoundly changed. This is discussed in detail in section 1.3. ⁴ Quantum entanglement is only one possible area that will cause our experience of reality to change radically. For example biotechnologies, nanotechnologies, artificial intelligence (AI) and human/AI interfaces to name some.
All Figures are copyrighted and re-used with permission.
Keywords: Hughes, Claire; Entangled; Installations (Art); New Zealand; Wellington; Virtual reality in art; Physics in art; Exhibitions; Quantum entanglement; Communication in science; 360603 Performance art